Like at Home. Tourism, Trauma Erosion and Nostalgia in the DDR Museum in Berlin - Panico, Mario (E|C, 2022)
This paper analyses the visiting experience presented to tourists in spaces devoted to the translation and transmission of the past, looking in particular at the nostalgia strategies proposed in spatial enunciation, i.e., the "softening" of events in museum halls. In this case, nostalgia is considered not so much (and not only) as an individual passion connected to the desire to return to a space, but as a spatial atmosphere to be consumed through the tourist experience. Nostalgia is also understood as a passionate coloring of museum strategies, that is used to make a past temporality experienceable and enduring, externalized as better than the present. The article takes a museum in Berlin as its case study, investigating the way in which the space tries to instill nostalgia in the tourist by recreating homely environments, producing a domestication of the past and a depotentiation of the trauma that underlies the history that is represented, making the experience playful and credible and thus still making the enunciated past desirable.